Weed science research in Uganda - Kikoba, E. (International Center for Tropical Agriculture, 1991)
Strategies adopted by weed researchers center on two aspects; cultural methods and chemical use. Cultural methods are intended to reduce weed competition through multiple and intercropping and high plant populations while herbicides reduce weed competition through the direct elimination of weeds. Weed control practices that use a combination of both methods may prove to be the most efficient in the control of annual and perennial weeds in Uganda. (AS)